Effect of pin profile on microstructure and mechanical properties of friction stir spot welded Al-Cu dissimilar metals. (December 2018) - Zhou, L.; Zhang, R.X.; Li, G.H.; Zhou, W.L.; Huang, Y.X.; Song, X.G.
Abstract: Pin profile exerts an important influence on heat production and material flow in friction stir spot welding, thereby affecting microstructure evolution and mechanical properties of the welded joint. Thus, the relationship between pin profiles and resultant microstructure of the joint as well as the mechanical properties needs to be revealed. In the present study, three types of tools with different pin profiles were designed to join aluminum and copper by friction stir spot welding. Optical microscope, scanning electron microscope and X-ray diffraction were conducted to characterize macrostructure and microstructure in welded joints. Tensile shear and microhardness test were used to evaluate the mechanical properties of joints. Well-formed joints were obtained using different tools under proper process parameters. Higher heat generation and temperature were produced during welding process by using threaded pin tool. Several intermetallic compounds, including CuAl2, CuAl and Al4 Cu9, were formed at the interface between aluminum and copper. No distinct difference was observed for microhardness distribution in the joints using various pin profiles. The tensile shear failure load was largely dependent on the pin profiles with the maximum value got in the joint obtained by using threaded pin. The tensile shear fracture of joint by using featureless pin presented the brittle fracture characteristics, and other welded joints showed the mixed fracture characteristics.